2011
DOI: 10.1371/journal.pone.0026693
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cardiac Ryanodine Receptor Channels by Alkaline Earth Cations

Abstract: Cardiac ryanodine receptor (RyR2) function is modulated by Ca2+ and Mg2+. To better characterize Ca2+ and Mg2+ binding sites involved in RyR2 regulation, the effects of cytosolic and luminal earth alkaline divalent cations (M2+: Mg2+, Ca2+, Sr2+, Ba2+) were studied on RyR2 from pig ventricle reconstituted in bilayers. RyR2 were activated by M2+ binding to high affinity activating sites at the cytosolic channel surface, specific for Ca2+ or Sr2+. This activation was interfered by Mg2+ and Ba2+ acting at low aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
(177 reference statements)
2
30
1
Order By: Relevance
“…However, at a SR voltage of 260 mV (similar as in Almassy et al, 2008), we observed flicker block and intermediate states of conductance (which could be attributed to short-lived substates) in RyR2 induced by K201. The blocking effect of K201 is intriguing, but the role of voltage dependence in RyRs has unknown physiologic significance as channels are thought to operate at a nearly constant SR voltage of ∼0 mV Diaz-Sylvester et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, at a SR voltage of 260 mV (similar as in Almassy et al, 2008), we observed flicker block and intermediate states of conductance (which could be attributed to short-lived substates) in RyR2 induced by K201. The blocking effect of K201 is intriguing, but the role of voltage dependence in RyRs has unknown physiologic significance as channels are thought to operate at a nearly constant SR voltage of ∼0 mV Diaz-Sylvester et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that RyRs activity heavily depends on luminal Ca 21 levels (Sitsapesan and Williams, 1998;Fill and Copello, 2002;Terentyev et al, 2002;Diaz-Sylvester et al, 2011;Porta et al, 2012). Although the effects of K201 on SR Ca 21 content appear to be mild under control conditions (Loughrey et al, 2007), the drug could have more significant effects under pathologic situations as in ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This heterogeneity results from the fact that some channels can dwell more often in high-open-probability (P o ) mode, characterized by long openings and short closures, while others display frequent low-P o mode, distinguished by frequent and brief flickering openings . RyRs dwelling in the high-P o mode were found to display increased sensitivity to physiologic agonists, lower sensitivity to blockers, and increased ability to associate with neighboring channels for coupled gating (Gyorke and Fill, 1993;Zahradnikova et al, 1999;Copello et al, 2002;Diaz-Sylvester et al, 2011;Porta et al, 2012). Thus, the domains in the RyR molecule involved in the stabilization of high-and low-P o modes have a huge significance for the synchronous gating of the channels.…”
mentioning
confidence: 99%